(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Antimony (Sb) is listed as a critical raw material in both Europe and the USA. Pyrometallurgical and hydrometallurgical methods are used for its recovery from raw sources. Hydrometallurgy is considered a suitable technology when Sb sources are low-grade ores or technogenic waste. After a brief introduction to the Sb species present in pregnant leach solutions (PLS) obtained by using different leaching reagents, this paper presents various methods for recovering Sb from PLS produced in the leaching hydrometallurgical stage. The discussion covers antimony recovery by hydrolysis and conversion, selective precipitation, crystallization, electrowinning, replacement, liquid-liquid extraction and ion exchange. Factors affecting the effectiveness of these processes and the recent attempts to improve these technologies are presented. Finally, possible future research directions are outlined.